รูปแบบการจัดการศึกษา “โรงเรียนสัมมาชีพ” สำหรับเด็กกลุ่มชาติพันธุ์บนพื้นที่สูง: กรณีศึกษาโรงเรียนสาธิตสังกัดมหาวิทยาลัยศรีนครินทรวิโรฒ แม่แจ่ม เชียงใหม่ - นาคสัมฤทธิ์ จรีพร (Journal of Education Studies, Chulalongkorn University, 2019)
The purposes of this study were to: 1) investigate the current and desired state of educational management for ethnic students in a highland school in Northern Thailand; and, 2) to present an educational management model. This research used quantitative and qualitative methods. The research tools were questionnaires and structured interviews. The data were analyzed by mean ( ), PNImodified and content analysis. The results showed that the average values of the desired state ( = 4.12) were higher than those of the current state ( = 3.72) in all broad areas. The desired state for educational management were granting credits for skills gained outside of school, standardized assessment, emphasis of both the career skills curriculum and core curriculum, flexible assessment methods, use of multi-media, demonstration of alternative ways for developing greater empathy among teachers, fostering innovation and pedagogy research. The school was found to utilize three systems. The desired educational management model for ethnic students focused on life skills and community based learning, fostering innovation, good career possibilities, a laboratory school for training purposes, flexible assessment methods, granting credits for skills gained outside school, develop greater empathy among teachers, fostering morals and unity, special educational standards, using tribal dialects and multi-media learning materials to reveal students’ potentials. These elements illustrated a model called “Ethical Career Demonstration School” that can be used as an educational model for ethnic students, where educational management develops the full capability of students and contributes towards self-reliance and a sufficiency economy based on philosophical theory.